Detecting Resemblance Of Orchid Plant Image Through Support Vector Machine (SVM) Of Kernel Linear Method - Susni Herwanti (Politeknik Negeri Lampung, 2014)
Tourism is a promising sector for the economic growth and social improvement. The development of tourism is able to create and improve employment opportunities, income, tax revenue the Government levy on the region, encourage increased investment and so on. One of the potential attractions for developed is ecotourism in the Bay of Kiluan. This important research is done to identify and assess the potential economic benefits of ecotourism of Kiluan Bay. The data were analyzed quantitatively as well as qualitatively through by the analysis of willingness to pay (WTP) visitors. The results showed that the tourism potential that can be developed was the island of kiluan, white sand, laguna, sightseeing tours, kiluan Gulf waters conservation education (tour of mangrove forests) and cultural tourism. The economic value of ecotourism of Kiluan Bay was 5.600.000.000 in 2014.Key words: ecotourism, Kiluan Bay, visitors, willingness to pay